KINERJA KARYAWAN DAN KEPENTINGAN WISATAWAN TERHADAP KUALITAS PELAYANAN JASA CV. CAN TOUR & TRAVEL - Bathari Nindita K., Rr.; Eka Mahadewi, Ni Putu; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2013)
CAN Tour & Travel is the new agent company so it’s need to find the satisfaction customer of quality service in this company. This paper will give input to improve company towards better. CAN Tour & Travel realize the tourist desire to provided services. Technique of determining the sample used in this research is the accidental sampling of 75 respondents. Data analysis techniques in this research used the analysis of quantitative and qualitative data analysis. Based on the research results have produced an average performance appraisal CAN Tour & Travel of 3.28 which means that the performance of CAN Tour & Travel is in excellent condition. And also generated an average rating of 3.51 valuation interest which means very important. There are various factors contained in determining tourist satisfaction is that the cleanliness and tidiness of employees, completeness and readiness of facilities, employee performance, employee's ability to communicate and provide information very well, timely and responsive to the needs and guest complaints, and build a good relationship with tourists itself. Discussion of the result obtained in this research that many performance factors that must be maintained and be prioritywith which should be further improved. It can be seen from the tourist’s perception of low performance with great interest.Result in this research can be recommended the CAN Tour & Travel giving great concern to employees in serving tourist.
Keywords: Performance, Interest, Satisfaction